Effect of crisis communication plans on crisis aversion in selected Nairobi Securities Exchange Companies - Kalei, Anne (International Journal Of Advanced Research in Engineering & Management (IJAREM), 2020)
This study aimed to establish the extent to which publicly listed companies in the Nairobi Securities Exchange (NSE)were adequately prepared for crisis situations by engaging in proactive crisis communication planning. I tlooked at the practice of crisis communication as key component of corporate communication. Corporates will be faced with a crisis one time or the other. When this happens, the corporates are forced to act. For some, strategies have already been put in place on how to roll out crisis communication plans, while others deal with the crisis in an ad hoc fashion. The study sought to review the various crisis situations that NSE-listed corporates have gone through. It additionally sought to find out if NSE-listed corporates had written crisis communication plans. The study also evaluated the various strategies employed by NSE-listed companies during crisis communication in a bid to establish best practice for proactive crisis communication for NSE-listed companies. A systematic random sampling was carried out. Self-administered questionnaires were issued to the respondents and SPSS (version 21) software was used to analyze the data. The study found out that NSE-listed companies were actually engaged in proactive crisis communication with written crisis communication plans and proactive non-crisis stakeholder relations being undertaken in order to draw goodwill from stakeholders during an actual crisis situation. The study, however, recommends the need for the listed companies to carry out periodic review and test runs of their crisis communication strategies.
Keywords: Crisis communication; Best practice; Nairobi Securities Exchange.